The Role of Political Stability in Foreign Investment Flows: Empirical Evidence from OIC Countries - Abdullah; Aisah, Laras; Basri (El-Barka Journal of Islamic Economics and Business, 2024)
This study aims to identify the determinants influencing foreign investment flows in the Organization of Islamic Cooperation (OIC) countries and to directly analyze the moderating effect of political stability. The research utilizes secondary data from 50 OIC countries covering the period from 2012 to 2022. The study adopts the Generalized Method of Moments (GMM) estimation technique to analyze the data. The findings reveal that inflation has a significant positive effect on foreign investment flows. Meanwhile, interest rates, labor force participation, and the Human Development Index (HDI) have significant yet non-positive effects. The HDI variable has a negative and insignificant effect. Furthermore, the political stability variable is able to strengthen the moderating influence of the interest rate on foreign direct investment, except for the inflation, labor force, exchange rate, and human development index variables. The conclusion, by incorporating the impact of political stability, governments can reduce political risks faced by investors and enhance their countries' attractiveness as credible investment destinations.